2015
DOI: 10.3390/molecules20023238
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Amorphigenin from the Seeds of Amorpha fruticosa against the Larvae of Culex pipiens pallens (Diptera: Culicidae)

Abstract: The larvicidal activity of the crude petroleum ether, ethyl acetate, acetone, chloroform and ethanol extracts of Amorpha fruticosa seeds was individually assayed for toxicity against the early fourth-instar larva of the mosquito, Culex pipiens pallens after 24 h exposure. Of the tested extracts, the ethanol one exhibited the highest larvicidal activity (LC50 = 22.69 mg/L). Amorphigenin (8'-hydroxyrotenone), a rotenoid compound which exhibits a strong larvicidal activity with LC50 and LC90 values of 4.29 and 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 70 publications
0
17
0
Order By: Relevance
“…For the assay of in vivo inhibition of the mitochondrial complex I activities, first, the fourth-instar larvae of Cx. pipiens pallens were exposed to sub-lethal concentrations of amorphigenin and rotenone [ 32 ] for 24 h, then isolated the mitochondria from the survival tested mosquito larvae and determined the mitochondrial complex I activity as described above. For the assay of in vitro inhibition of the mitochondrial complex I activities, 10 μL of different concentrations each of amorphigenin and rotenone were prepared in alcohol and diluted in 25 mM phosphate buffer (pH 7.2), then mixed with 10 μL of the mitochondria.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the assay of in vivo inhibition of the mitochondrial complex I activities, first, the fourth-instar larvae of Cx. pipiens pallens were exposed to sub-lethal concentrations of amorphigenin and rotenone [ 32 ] for 24 h, then isolated the mitochondria from the survival tested mosquito larvae and determined the mitochondrial complex I activity as described above. For the assay of in vitro inhibition of the mitochondrial complex I activities, 10 μL of different concentrations each of amorphigenin and rotenone were prepared in alcohol and diluted in 25 mM phosphate buffer (pH 7.2), then mixed with 10 μL of the mitochondria.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous study [ 31 ] showed that ethanol extract from seeds of A. fruticosa had good contact effect and antifeedant activity against Schizaphis graminums (Homoptera: Aphididae). Then, amorphigenin, a rotenoid compound which exhibits a strong larvicidal activity with LC 50 and LC 90 values of 4.29 and 11.27 mg/L, respectively, was isolated from the ethanol extract by column chromatograpy [ 32 ]. However, up to now little is known about inhibition effect of amorphigenin on mosquito larvae.…”
Section: Introductionmentioning
confidence: 99%
“…Essential oils and their constituents have been recommended as alternative sources for insect control, predominantly because some are selective, biodegrade to nontoxic products, and have minimal impacts on non-target organisms and the environment [ 6 ]. Many essential oils and constituent compounds that come from various essential oils can put forth toxic activity against mosquito species [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. During our screening project for new agrochemicals from the wild plants and Chinese medicinal herbs, essential oil of Echinops grijsii Hance (syn.…”
Section: Introductionmentioning
confidence: 99%
“…In China, A. aegypti is considered one of the major vectors for the transmission of dengue fever (common clinical characteristics as fever, headache, chilly, joint pain) and C. pipiens pallens is the primary vector of wuchereriasis and epidemic encephalitis B (clinical symptoms included high fever, nausea and vomiting, altered consciousness) [1,2]. Currently, synthetic insecticides and insect growth regulators are widely applied to control larval mosquitoes [3].…”
Section: Introductionmentioning
confidence: 99%
“…The mosquitoes, Aedes aegypti L. and Culex pipiens pallens Coquillett (Diptera: Culicidae) are two worldwide insects causing dreadful nuisance and transmitting many dangerous diseases [1,2]. In China, A. aegypti is considered one of the major vectors for the transmission of dengue fever (common clinical characteristics as fever, headache, chilly, joint pain) and C. pipiens pallens is the primary vector of wuchereriasis and epidemic encephalitis B (clinical symptoms included high fever, nausea and vomiting, altered consciousness) [1,2].…”
Section: Introductionmentioning
confidence: 99%